Persepsi Wajib Pajak Tentang Kualitas Infrastuktur Jalan dan Jembatan terhadap Kemauan Membayar Pajak dengan Transparansi Informasi sebagai Variabel Moderasi - Febriani, Aulia; Fakhroni, Zaki (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this research is to obtain empirical evidence on taxpayers' perceptions of the influence of road and bridge infrastructure quality on tax payment willingness with information transparency as a moderating variable. This type of research is quantitative using primary data and purposive sampling method with a total of 130 respondents. Data analysis uses SEM-PLS assisted by SmartPLS Version 3 program. The results of this research provide empirical evidence that: (1) Taxpayers' perception of road infrastructure quality influences tax payment willingness; (2) Taxpayers' perception of bridge infrastructure quality does not influence tax payment willingness; (3) Information transparency does not affect tax payment willingness; (4) Information transparency cannot moderate the relationship between taxpayers' perception of road infrastructure quality and tax payment willingness; (5) Information transparency cannot moderate the relationship between taxpayers' perception of bridge infrastructure quality and tax payment willingness. Keywords: Information Transparency, Road And Bridge Infrastructure Quality, Taxpayers' Perception, Willingness To Pay Taxes.